To your eternity. 13 - Oima, Yoshitoki (Kodansha Comics, 2020)
"Several centuries have passed since the siege of Renril, and now, mankind celebrates a peaceful world. In an era free of the menacing Nokkers, the battles of Fushi and his comrades are relegated to mere legend. One day, Fushi reawakens to cars speeding down streets, wires hanging suspended in the sky, neon lights aglitter... What else could lie in wait?"--Provided by publisher.